Effectiveness of the Er,Cr:YSGG Laser in the Removal of Oral Plexiform Neurofibroma (Case Report) - Zainab Fadhil Odah,; Hanan Jafer Taher,; AlAlawi, Ammar (Iraqi Journal of Laser, 2024)
Background: Plexiform neurofibroma [PN] is a non-malignant tumor that affects the peripheral nerve sheath and is associated with neurofibromatosis type 1 [NF1.1]. Because they are infiltrative, plexiform neurofibromas can be difficult to cure. Laser therapy has emerged as a potentially effective approach for the management of oral plexiform neurofibromas, rendering it a valuable diagnostic tool within the field of dentistry.Case Study Presentation: A male patient, aged 60, diagnosed with NF1, presented with painless swellings of the mandibular left edentulous alveolar ridge, which was causing difficulty in wearing a denture. The tumor was diagnosed as an oral plexiform neurofibroma. The entire lesion was excised surgically using an Er,Cr:YSGG laser system with specific parameters to minimize thermal damage to the surrounding tissues. Histological analysis confirmed the diagnosis of plexiform neurofibroma, with minimal thermal damage and desiccation observed at the excision margin.Conclusion: The utilization of the Er,Cr:YSGG laser [2780 nm] for excision biopsy of plexiform neurofibroma led to exceptional postoperative healing and minimal thermal damage to the tissue. The laser's ability to precisely ablate the target tissue while minimizing damage to the surrounding structures was crucial in preserving the integrity of the specimen for histopathological analysis.